(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article examines the current topic of studying the language of Russian proverbs and sayings in the context of Russian language classes, and also considers the use of these language units when teaching students in non-Russian linguistic groups. The purpose and objective of this article is to increase the motivation for learning the Russian language and the success of its acquisition through the use of Russian proverbs and sayings.